The Relationship Between Motivation for Learning and Academic Achievement among Basic and Advanced Level Students Studying Chinese as A Foreign Language in Years 3 to 6 at Ascot International School in Bangkok, Thailand - Li, Ting; Lynch, Richard (Scholar: Human Sciences, 2016)
The purpose of this study was to determine the level of motivational goal orientation, and the relationship between the motivational goal orientation and academic achievement among basic and advanced level students studying Chinese as a foreign language in years 3 to 6 at Ascot International School in Bangkok, Thailand. The study respondents were 127 students studying Chinese as a foreign language in years 3 to 6 at Ascot International School in 2014. This study followed a quantitative research methodology employing both a questionnaire and unit quizzes to address the research objectives. There were two main parts included in the study: the level of motivational goal orientation and the relationship between motivational goal orientation and academic achievement among basic and advanced level students. In this study, the motivational goal orientation focused on intrinsic and extrinsic goal orientation. Based on the study objectives, there were eight main findings: 1) the level of intrinsic goal orientation of the basic class was high; 2) the level of intrinsic goal orientation of the advanced class was high; 3) the level of extrinsic goal orientation of the basic class was high; 4) The level of extrinsic goal orientation of advanced class was very high; 5) no significant relationship was found between intrinsic goal orientation and academic achievement among basic class students; 6) there is a significant relationship found between the intrinsic goal orientation and academic achievement among advanced class students; 7) there is a significant relationship found between the extrinsic goal orientation and academic achievement among basic class students ; 8) there is a significant relationship found between the extrinsic goal orientation and academic achievement among advanced class students.